Can business ethics be taught? - Mhd. Sarif, Suhaimi (2010)
MGT 3020 Business Ethics is one of the university required courses for students of Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia. Some academics and students believed that Business Ethics cannot be taught due to many reasons. This study aims to obtain the views of current Business Ethics students whether they Business Ethics can be taught or otherwise. The study was conducted on 136 Business Ethics during their respective class time on a specified answer sheet of a half size of A4 paper. The students’ opinions on the answer sheet were analyzed using content analysis technique. The findings showed that only 15% (20 out of 136) of Business Ethics students believed that Business Ethics cannot be taught. They argued that logically people learnt about personal ethics and business ethics based on the practices that they experienced for instance when they got caught and penalized. However, majority of the students believed that Business Ethics can be taught based on theoretical and practical approaches. For future research, the study should be extended to former Business Ethics who used to learn the course to validate the opinions of current Business Ethics students. Moreover, the future study also should obtain views from the course instructors of Business Ethics of all public universities in Malaysia.